Transonic aero-acoustics of weapon bays - Bacci, David (Cranfield University, 2017)
The requirement for modern combat aircraft to have low radar cross sections and improved aerodynamic performance has introduced the necessity to incorporate weapons bays in almost every new military aircraft design project. This, on its own, has led to a renewed interest in the field of cavity flows, especially during transonic and supersonic speed regimes. Although considerable data already exist on the fundamental physical aspects of cavity flows, whenever a cavity is integrated in an aircraft design, various other related issues must also be considered. Airframe aerodynamics requirements may impose changes on the shape of the cavity, while flight dynamics parameters, like incidence and sideslip, may prompt a different response of such a non-linear phenomenon. A study was therefore conducted in order to assemble knowledge and understanding of some of the main aspects related to weapon bay design. A representative cavity, exposed to a typically representative transonic Mach number, was tested to determine the effects of the introduction of typical stealth design features. These included the saw-toothing of the leading and trailing edges of the bay and the indentations of the doors accompanying the cavity. Such features were tested with and without the presence of a model of a representative store inside the bay. Subsequently, these aspects were tested, in numerical models, by installing the cavity on a representative stealthy airframe, which was used to explore incidence angle effects of the flow characteristics. Finally, an innovative solution, designed to mitigate the adverse aspects of the flow was tested. Due to the extreme complexity of the aero-acoustic environment typical of cavity flows, a technique based on the complementary use of frequency-domain and time-frequency domain linear and non-linear analyses was used to process the pressure histories recorded. Such a procedure was able to highlight the complexity of the flow, which, in accordance with previous studies, was rich in non-statistical stationary phenomena, like amplitude modulation, frequency modulation, and mode switching.